The Portuguese online wine buying consumer : characteristics, motivations and behaviour - Santos, José de Freitas (2012)
Purpose – This purpose of this paper is to investigate the main characteristics, buying habits, motivations, influences, and overall satisfaction of Portuguese online consumers of wine, as well as to assess whether this market segment can be considered a niche. Design/methodology/approach – A survey was conducted in a Portuguese online wine shop during the last three months of 2009. The questionnaire included questions about the consumers’ socio-demographic characteristics, motivations, buying habits and factors influencing online buying behaviour. The questionnaires were delivered by e-mail to regular and new customers when a transaction was processed online. Of the 82 questionnaires received, 74 were sufficiently complete to be used in the study. Findings – The online wine market can be considered a niche in Portugal. As the authors’ empirical work shows, this segment is mainly composed of young, male, well-educated, high-income consumers who buy wine online from home often less than once a month. They are motivated by convenience, a wider selection of wines, availability, and price. As decision factors, they value the origin/brand of the wine, the price, the recommendation of the online shop, and their own experience. A comparative analysis with international online wine consumers found differences based on profile and consumer buying behaviour (patterns and influences). Research limitations/implications – The non-probabilistic sample contained only data from a Portuguese online wine store. Thus, future studies should examine other online wine stores to determine the level of generalisation of the findings to the entire community of online wine consumers. Originality/value – To the best of the authors’ knowledge, this is the first research conducted in Portugal to identify the main characteristics, buying habits, motivations, influences, and overall satisfaction of the Portuguese online consumers of wine. The paper provides useful insights into the topic, as well as a basis for future studies.